Treatment of children with mobile flat feet with modified Kidner operation (Texas Journal of Multidisciplinary Studies, 2024)
In this article, a new modified Kidner's operation is used to treat flat feet, a common disease in children, so that children with flat feet can get up early without complications and get rid of flat feet so that children can walk on healthy feet.